Games Based Model of Volleyball Passing Exercise for Junior High School Student (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
The purpose of the study was to develop a model of volleyball passing exercise through games. The study used qualitative and quantitative using Research and Development from Borg and Gall which consists of ten stages. The subject in this research is junior high school student in Makasar. Data were collected through interview and questionnaire. Data analysis was done descriptively, qualitatively and quantitatively. The results of finding show that games have given exercise variation which makes some students interest and fun when they do volleyball passing exercise. The model has twenty types of games in volleyball passing exercise.